WUJUD KIAS DALAM TAMBO MINANGKABAU - M. Hum, Yendra SS (Jurnal Gramatika, 2016)
AbstractResearch on kias in Tambo Minangkabau’s focused on the study of figurative forms and and forming figurative inspiration. This research aims to explain any forms of figurative and the inspiration forming figurative in Tambo Minangkabau. Based on the analysis conducted, figurative forms are identified into simile, metaphor, personification, alegori, parabel, sinekdoke, epitet, eponim, paranomasia, and  antonomasia. Forms of figurative metaphors are identified form the most dominant form of variations convey stories in Tambo Minangkabau. Pattern conception of Minangkabau community built through forms and characteristic of nature that prefigured to all aspects to serve the teaching and philosophy of life and then poured into Tambo Minangkabau. Minangkabau  people whose way of thinking is metaphorical. This is a manifestation of the philosophy of  “Alam Takambang Jadi Guru”. Conceptual relationship of linguistic form with dimensions of the socio-cultural seen in relation of meaning. That is mean linguistic patterns are always associated with patterns of socio-cultural speech community including culture that inspired the metaphors in the text of Tambo Minangkabau. the inspiration forming figurative are activity or process of acquiring knowledge and poured into Tambo Minangkabau and became a source of teaching, rule, custom, and culture. forming figurative inspiration in TM are figurative inspiration from nature, figurative inspiration from objects (tool),  figurative inspiration from animals, inspiration from pattern of human bodies, and inspiration from the concept of religion. AbstrakPenelitian mengenai kias dalam Tambo Minangkabau difokuskan pada kajian bentuk kias dan inspirasi pembentuk kias dalam Tambo Minangkabau. Penelitian ini bertujuan untuk menjelaskan apa saja bentuk-bentuk kias dan menjelaskan inspirasi pembentuk kias yang terdapat dalam teks Tambo Minangkabau. Berdasarkan analisis yang telah dilakukan, bentuk-bentuk kias yang teridentifikasi antara lain seperti simile, metafora, personifikasi, alegori, parabel, sinekdoke, epitet, eponim, paranomasia, dan antonomasia. Dari bentuk-bentuk kias yang teridentifikasi bentuk metafora merupakan bentuk yang paling dominan sebagai variasi penyampai cerita.  Pola konsepsi masyarakat Mk dibangun melalui bentuk, sifat, dan ciri alam yang dimetaforakan ke segala aspek kehidupan untuk dijadikan pengajaran dan pandangan hidup yang dituangkan kedalam Tambo. Cara berfikir orang Mk yang bersifat metaforikal Ini merupakan perwujudan dari filosofi  Alam Takambang Jadi Guru yang dianut oleh masyarakat Mk. Hubungan konseptual bentuk linguistik dengan dimensi lingkungan sosio-kultural terlihat antar hubungan makna. Artinya, pola-pola linguistik selalu berhubungan dengan pola-pola sosio-kultural masyarakat penutur, termasuk budaya masyarakat MK yang menjadi sumber inspirasi kias dalam teks TM. Inspirasi pembentuk kias  ini merupakan kegiatan atau proses memperoleh pengetahuan termasuk kesadaran dan perasaan atau usaha mengenali sesuatu melalui pengalaman sendiri dan juga sebagai proses sosial, pengenalan, dan penafsiran lingkungan oleh orang Mk sebagai hasil pemerolehan pengetahuan yang kemudian dituangkan kedalam teks TM yang kemudian menjadi sumber dari pengajaran, aturan, adat, dan budaya Mk. Yang menjadi sumber inspirasi pembentuk kias dalam TM adalah inspirasi kias dari alam, inspirasi kias dari benda, inspirasi kias dari binatang, inspirasi kias dari anggota tubuh, dan inspirasi kias dari konsep agama. Keywords: Tambo, Minangkabau, Kias.